Evaluasi dan Perbaikan Desain Antarmuka Pengguna Situs Web Persela Store dengan Menggunakan Metode Human Centered Design (HCD) - Yahya Vernanda Ramadhani; Hanifah Muslimah Az-Zahra; Yusi Tyroni Mursityo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Persela Store is a retail unit formed as the Official Store of the Persela Lamongan football club which aims to increase product sales and income from the team and make it easier for Persela Lamongan fans (suppourter) to get information and purchases about the latest products from Persela. Through interviews with stakeholders or the person in charge of the Persela Store, a problem was found, namely the Persela Store website since it was first launched in 2018 has never been evaluated and improved at all so that it has an impact on the number of visitors who shop through the Persela Store website which is very few and less than optimal. The purpose of this study is to determine the value of differences in user satisfaction before the evaluation of the improvements and after the evaluation of the design of the solutions. Based on the problems found, this study will evaluate using Tree Testing to assess website navigation based on aspects including Success Rate, First Click, Directness, Time Spent, and Destination. In evaluating user satisfaction displays will use the System Usability Scale (SUS) which aims to determine the value of user satisfaction based on the value of Aspectibility Ranges, Grade Scale, Adjective Range, and Percentile Rank. In designing the solution design through the Close Card Sorting method as a reference for the structure of determining the layout of the website flow based on the expectations of the user, with the final result a sitemap and in accordance with usability guidelines. This research process as a whole applies the Human Centered Design (HCD) approach where each process coordinates and gets approval from stakeholders and users. The final results and conclusions in this study are evaluation values ​​based on user testing, recommendations for improvement designs based on user expectations with usability guidelines in the form of Prototype High Fidelity. The results of the final evaluation of the Success Rate value of 100%, Dirrectness 95.55%, Time Spent 4.13 seconds, First Click 100%, Destination 100%, and an increase in user satisfaction values ​​based on the increase in Acceptability Ranges values, namely Acceptable, Grade Scale category B, Adjective Rating for the Best Imaginable category, and Percentile Rank for category A.